A influência do infiltrado de gordura muscular e da composição corporal no controle postural em pacientes com osteoartrite de joelho - Pedroso, Maria Gabriela (Universidade Federal de São Carlos, 2019)
The aim of this thesis was to investigate the amount of fat infiltrate in the thigh and trunk and its association with postural control and functional capacity in people with knee osteoarthritis (OA). Thus, three studies were performed: Study I: Fatty infiltration in thigh muscles in knee osteoarthritis: a systematic review and meta-analysis; Study II: Infiltration of adipose tissue in the thigh of patients with knee osteoarthritis influences changes in postural control; Study III: Relationship between trunk composition and physical function in non-obese individuals with knee osteoarthritis. Methods: In the first study, the systematic review was performed by searching in scientific databases The methodological quality of the articles selected was assessed by Downs and Black checklists and the meta-analysis was performed through RevMan software. For study I and II, twenty-seven non-obese subjects with knee OA, aged 40-65 years were matched by age and BMI with twenty-two individuals without knee OA. The thigh and trunk composition was evaluated by computed tomography, segmented into: subcutaneous fat, intermuscular fat and muscle. Muscle attenuation was used to evaluate the muscular fatty infiltration. In study II; the postural control was evaluated through a force platform, where the subjects remained in orthostatic in a firm surface with open and closed eyes and in a soft surface with open and closed eyes. The differences between groups for the postural control variables were tested by Student's test and Man-Whitney. The thigh composition was evaluated by MANCOVA. Spearman's correlation was used to evaluate the correlation between thigh composition and postural control parameters. The influence of thigh fat infiltrate on postural control was assessed by multiple linear regression analysis. In study III, the muscle attenuation mean was used to measure the muscular fatty infiltration; the physical function was assessed through the sit-to-stand, 40 m walk, and stair climbing tests. The differences between the groups for the trunk composition variables were evaluated using the MANCOVA test, while the physical performance was evaluated by Student's test. A Pearson correlation test was performed to evaluate the correlation between trunk composition and physical performance. Results: In study I, 7 studies were selected for systematic review and 6 were included in the meta-analysis. The common variable of all studies was intermuscular fat. The studies were of good quality, and the meta-analysis showed that people with knee OA have greater amounts of intermuscular fat than healthy individuals, as shown by a standardized difference of averages of 0.39 (95% CI 0.25 to 0.53). In study II we found that individuals with knee OA had a greater amount of muscle fat infiltration. The muscle fatty infiltration was able to explain up to 52% of the variability of the postural control of people with knee OA. In Study III we found that individuals with knee OA have a greater cross-sectional area of subcutaneous fat, intermuscular, muscle fat infiltration and smaller muscle area in the trunk. Among the components of the trunk composition, the muscular fatty infiltration showed a greater correlation with the performance in the physical function tests. Conclusion: The results indicate that individuals with knee OA have greater fat infiltration in the musculature of the thigh and trunk. The accumulation of fat infiltration in the thigh may explain part of the decrease in postural control presented by individuals with knee OA, whereas the accumulation of fat in the trunk is associated with the deficit of the physical function of this population
Influence of muscular fat infiltration and body composition in postural control in patients with knee osteoartrite
Keywords: Artrite; Composição corporal; Equilíbrio; Capacidade funcional; Tecido adiposo; Arthritis; Body composition; Balance; Physical function; Adipose tissue; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL